Increased corticospinal excitability induced by unpleasant visual stimuli - Coelho, C.; Lipp, Ottmar; Marinovic, W.; Wallis, G.; Riek, S. (Elsevier, 2010)
Pleasant and unpleasant emotional stimuli are frequently conceptualized as motivators for action. This notion was examined using focal transcranial magnetic stimulation (TMS). Ten healthy participants viewed pleasant, neutral, and unpleasant pictures from the International Affective Picture System (IAPS). During picture viewing, focal TMS was applied to the right motor cortex over the area innervating the first dorsal interosseous muscle of the left hand. Corticomotor excitability was larger while viewing negative pictures than while viewing neutral or positive images, as evidenced by greater motor evoked potentials. No difference was found between pleasant and neutral pictures. These results are consistent with models of emotion in which the neural networks underlying negative emotions have selective, direct connections to brain structures that mediate motor responses. © 2010.